Analisis Psikologi Tokoh Utama dalam Novel Bidadari Karya Pipiet Senja - Asih Ria Ningsih; Hermawan Hermawan; Nika Erlina (Jurnal Bahasa dan Sastra, 2022)
Novels include many problems of everyday life. This is also what is in the novel Bidadari by Pipiet Senja. The novel shows the unusual events of a woman, namely from the psychological side of the main character played by Soli. The Bidadari novel shows the psychology of the main character about physiology, security, love and belonging, self-esteem, and self-actualization. This study aims to describe the psychology of the main character in the novel Bidadari by Pipiet Senja. This type of research is a qualitative research. The results showed that the psychology of the main character found was as follows: first, there were 16 physiological needs. Second, the need for security is 10 data. Third, the need for love and taste has as many as 42 data. Fourth, the need for self-esteem as much as 6 data. Fifth, the need for self-actualization as many as 8 data. Based on the results of the study, it can be concluded that the most dominant psychology of the main character found is the need for love and belonging. The least psychology of the main character is the need for self-esteem.